2017
DOI: 10.3389/fmicb.2017.00644
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Centric Analysis of a Thermophilic and Cellulolytic Bacterial Consortium Derived from Composting

Abstract: Microbial consortia selected from complex lignocellulolytic microbial communities are promising alternatives to deconstruct plant waste, since synergistic action of different enzymes is required for full degradation of plant biomass in biorefining applications. Culture enrichment also facilitates the study of interactions among consortium members, and can be a good source of novel microbial species. Here, we used a sample from a plant waste composting operation in the São Paulo Zoo (Brazil) as inoculum to obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 87 publications
(150 reference statements)
2
36
0
1
Order By: Relevance
“…Genera Paenibacillus, Pseudomonas, Terrisporobacter, Actinomyces, Geofilum, Lachnoclostridium, Cryseobacterium, Oscillibacter, Acetivibrio, and Parabacteroides were found in lower abundances among core microbes (Nelson et al, 2011;Shida et al, 2012;Lee et al, 2013;Yan et al, 2013;Cho et al, 2015;Pap et al, 2015;Sun et al, 2016;Gagliano et al, 2017;Lemos et al, 2017;Nakajima et al, 2017;Neshat et al, 2017;Tian et al, 2017) (Supplementary Table 2).…”
Section: The Core Microbial Communitymentioning
confidence: 99%
“…Genera Paenibacillus, Pseudomonas, Terrisporobacter, Actinomyces, Geofilum, Lachnoclostridium, Cryseobacterium, Oscillibacter, Acetivibrio, and Parabacteroides were found in lower abundances among core microbes (Nelson et al, 2011;Shida et al, 2012;Lee et al, 2013;Yan et al, 2013;Cho et al, 2015;Pap et al, 2015;Sun et al, 2016;Gagliano et al, 2017;Lemos et al, 2017;Nakajima et al, 2017;Neshat et al, 2017;Tian et al, 2017) (Supplementary Table 2).…”
Section: The Core Microbial Communitymentioning
confidence: 99%
“…Among the recovered genomes, ZC4RG01 (s__Caldibacillus debilis),, ZC4RG04 (s__T. bispora),, ZC4RG13 (s__Rodothermus marinus),, ZC4RG21 (s__Thermobi da fusca),, ZC4RG26 (s__Sphaerobacter thermophilus),, ZC4RG32 (s__Caldicoprobacter faecalis),, and ZC4RG49 (s__[Clostridium] cellulosi) have been classi ed as species previously reported as being capable of cellulose degradation [11,[30][31][32][33][34][35]. Two Chloro exi MAGs, ZC4RG36 (c__Anaerolineae) and ZC4RG48 (f__Rosei exaceae), are additional lignocellulose degraders that we have found, having many CDSs classi ed as CAZymes (326 and 313, respectively), exceeding the number of CAZymes in the much better-known lignocellulose degraders T. bispora [36] and T. fusca [37], corresponding to ZC4RG04 and ZC4RG21, with 174 and 150 CAZymes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We compared the 60 MAGs with genomes recovered from our previous studies [3,11] and between both composting cells (Supplementary Table S2b). We observed that a few genomes can be said to be present (using the same methodology for MAG species assignment) in different samples, although the majority was found in only one sample.…”
Section: Presence Of Mags In Other Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermophilic conditions have additional benefits of high substrate degradation rate, pathogen removal, and efficient heat utilization of SOWs. The thermophilic microbial consortium also harbors distinct microbial species that possess metabolic functions related to biomass degradation and utilization [12,13]. Therefore, a TAD system fed with SOWs can be rewired to an acetate-producing system by inhibition of methanogenesis.…”
Section: Introductionmentioning
confidence: 99%